Driving Teacher Professionalism Through Human-Centric Leadership: Evidence From a Qualitative Case Study in an Indonesian Elementary School - Puji Mulyani; Widya Kusumaningsih; Qristin Violinda (Universitas Negeri Surabaya, 2026)
School principals play a crucial role in shaping teacher performance through their managerial skills. This study examines the impact of technical, human, and conceptual skills on teacher effectiveness, focusing on motivation, classroom management, and instructional quality. A qualitative case study approach was employed, utilizing interviews, observations, and document analysis to gather data from a primary school. The findings reveal that human skills, particularly communication and teacher support, have the most significant influence on teacher performance, fostering a collaborative and engaging learning environment. The study highlights challenges such as administrative burdens and resistance to change among teachers, which hinder effective school leadership. These findings provide valuable insights for policymakers and educators in designing targeted interventions to strengthen school leadership and teacher effectiveness. By addressing these areas, schools can create a more adaptive and dynamic learning environment that benefits both teachers and students.